Nyutdannede sykepleieres oppfatninger om tverrprofesjonell og tradisjonell studentpraksis som arena for tilegnelse av trygghet på rolle og ansvar - Kari Anita Furunes; Hildfrid V. Brataas (Septentrio Academic Publishing, 2014)
The article deals with recently graduated nurses' perceptions of traditional practical studies during the last year of the nurse education, and of practical studies in a cross-professional student-run rehabilitation center. The purpose was to gain knowledge about how nurses feel the two forms of practical studies contribute to role confidence and feeling of competence for interdisciplinary collaboration in inexperienced nurses.Method: A qualitative descriptive and interpretive pilot study was conducted. Narrative interviews with nurses were done two years after graduation. Thematic content analysis was done.Results: The nurses highlighted that practical training in taking nursing responsibilities was of importance in preparation for employment. Graduate nurses who only had had traditional practical studies felt role uncertainty and stress. Those who had interdisciplinary team based practical studies before the transition to working life had experienced trade role learning and collaborative learning during these studies. That learning process contributed to a feeling of role confidence in the inexperienced nurse.Conclusion: Practical studies where interdisciplinary student groups are training on team-based collaboration appear to promote inexperienced nurses' confidence in interdisciplinary collaboration and in the professional role. The study is a pilot study with few informants. There is a need for research that provides knowledge about the learning outcomes of different practice models on preparation for professional work.